Tindak Tutur Direktif Bermodus Imperatif Siswa dalam Proses Pembelajaran Bahasa Indonesia di SMK - Fajrin Nur Jannah; Rusdhiyanti Wuryaningrum (Nuances of Indonesian Language, 2022)
This study aims to describe the imperative mode of directive speech acts of students in the Indonesian language learning process at SMK Negeri 5 Jember. Speech acts are used as the focus of the study by utilizing the learning process in the classroom. The data used in this study are speech segments containing directive speech acts with the imperative mode of students and their context. Observation technique is a data collection technique used in this study. The source of the data used in this research is directive speech acts with the imperative mode of students in the learning process. The results of this study indicate that in the process of learning Indonesian at SMK Negeri 5 Jember, various types of directive speech acts with imperative mode are found, including directive speech acts of advocating, requesting, prohibiting, and urging imperative mode. Then it was also found that the function of the directive illocutionary act with an imperative mode which includes the function of the directive illocutionary act of asking, ordering, requesting, and giving advice. In addition, it was also found that the strategies used were direct literal and indirect literal speech act strategies with imperative mode.